الإمامة عند الإباضية في عمان - الخروصي, عبدالعزيز بن هلال بن زاهر (مجلة تاريخ المغرب العربي, 2016)
إنّ الحكم الإسلامي الذي أقامه الرسول صلى الله عليه وسلم بعد الحدث التاريخي، حدث الهجرة المباركة من مكة المكرّمة مسقط رأسه إلى المدينة المنورة، شكّل حدثاً عظيماً في تاريخ الأمة العربية ـ الإسلامية ؛ إذ أنه كان منطلقاً لقيام الدولة الإسلامية التي أسسها الرَّسول محمد صلى الله عليه وسلم ومن هنا كانت الإمامة، تمثيلاً حياً وتطبيقاً عملياً للخلافة القائمة على حكم الشورى، وانتخاب الحاكم من بين أفراد الشعب أو من خلال من يراهم الرعية ممثلين حقيقيين لهم ، ممّن يُعرفون بأهل الحلّ والعَقْد ، عند جل المذاهب الإسلامية.
Keywords: Imamat -- Oman

To govern the Omani Ibadi Society in the 17th to 19th century: Some documentary and textual evidence on the governor-related relationship and the Omani Ibadi Identity - Andriyanova, Olga (Islamic governance in South Arabia: the imamate in Yemen and Oman, 2016)
The idea of a “caliphate” has become a controversial model for a Muslim state. But imamates, or caliphates, existed in South Arabia until the 1950s and early 1960s, in the form of a Zaydi Shi’i imamate in Yemen and an isolated Ibadi imamate in Oman. Both traditions left strong traces in the legal structure and court system of the two states, in addition to various experiences and views on what the imamate is or was. While the differences between the imamate in Zaydism and Ibadism are decisive, similarities have never been the focus of a comprehensive study. This seminar/workshop will focus on various aspects of governement in a historical and Islamic legal perspective. It will consist of two presentations on Oman and Ibadism by PhD student Olga Andriyanova (University of Paris 1) and Post doc Anna Rita Coppola (University of Rome La Sapienza) as well as short presentation by Eirik Hovden (researcher, AHKR, UiB) on the Zaydi imamate.
Keywords: Imamat -- Oman

The Ibadi Imamate: its meanings and role and the Omani historiography - Coppola, Anna Rita (Islamic governance in South Arabia: the imamate in Yemen and Oman, 2016)
The idea of a “caliphate” has become a controversial model for a Muslim state. But imamates, or caliphates, existed in South Arabia until the 1950s and early 1960s, in the form of a Zaydi Shi’i imamate in Yemen and an isolated Ibadi imamate in Oman. Both traditions left strong traces in the legal structure and court system of the two states, in addition to various experiences and views on what the imamate is or was. While the differences between the imamate in Zaydism and Ibadism are decisive, similarities have never been the focus of a comprehensive study. This seminar/workshop will focus on various aspects of governement in a historical and Islamic legal perspective. It will consist of two presentations on Oman and Ibadism by PhD student Olga Andriyanova (University of Paris 1) and Post doc Anna Rita Coppola (University of Rome La Sapienza) as well as short presentation by Eirik Hovden (researcher, AHKR, UiB) on the Zaydi imamate.
Keywords: Imamat -- Oman